Solar photocatalytic and surface enhancement of ZnO/rGO nanocomposite: degradation of perfluorooctanoic acid and dye - Chin, Boon Onga; Mohammad, Abdul Wahab; Law, Yong Ng; Mahmoudi, Ebrahim; Azizkhani, Sepehr; Hairom, Nur Hanis Hayati (Elsevier B.V., 2017)
In this work, ZnO/rGO nanocomposites (NCs) were synthesized through a low temperaturesol–gel method. Zinc oxide decorated on graphene sheets could provide surface enhance-ment and hinder the rapid recombination rate of electron hole pairs that occur during aphotocatalysis process. It has been observed that the loading of ZnO decorated on graphenesheets is important in controlling the morphologies and surface enhancement of ZnO/rGONCs. Field Emission Scanning Electron Microscope (FESEM) micrographs reveal that spheri-cal shape and hexagonal-based nanopyramid of ZnO can be formed at low and high loadingof ZnO, respectively. NCs showed excellent performance for degradation of perfluorooc-tanoic acid (PFOA) and methyl orange in aqueous solution under solar irradiation. Herein,mechanisms for the formation of different shapes of ZnO nanostructures decorated ongraphene and their enhancement towards surface and photoactivity were discussed indetails.